Synthesis and application of zinc oxide nanoparticles in Pieris brassicae larvae as a possible pesticide effect - Isabella Martins Lourenço; Amedea Barozzi Seabra; Marcelo Lizama Vera; Nicolás Hoffmann; Olga Rubilar Araneda; Leonardo Bardehle Parra (AIMS Molecular Science)
Pieris brassicae is commonly known as the cabbage moth and is a species known to be invasive, thereby causing serious damage to vegetables and subsequently leading to total crop loss. Formulations of nanopesticides can provide unique characteristics such as size and shape, in addition to having integrated properties in a single material, making them efficient in pest management and protection against diseases in a single material; it can be applied in small volumes, with a greater precision, lower input costs, and a potential reduction in environmental contamination. Nanotechnology is a type of alternative and highly effective technology in several sectors, mainly in agriculture and the enrichment and fortification of cultivars. Hydrothermal synthesis is a type of process used to obtain nanoparticles with a more uniform crystallinity and aging of nanocrystallites, where high temperatures and pressures help to reduce particle aggregation. Chemically synthesized metal nanoparticles, such as zinc oxide nanoparticles (ZnO NPs), can find wide applications and success against different types of pests, such as larvae. The present study focuses on the application of different concentrations of ZnO NPs (12.5, 25, 50, 100, 200 and 400 mg/L) on the body surface of P. brassicae to verify their possible pesticide activity against these larvae. The results of this study suggest a non-intuitive pesticidal activity of ZnO NPs against cabbage moth larvae. The highest mortality percentage of larvae against the treatments occurred at the concentration of 200 mg/L of ZnO NPs, represented by a rate of 100% in the 72-h period of the experiment. Finally, the results of the present study with ZnO NPs and P. brassicae larvae suggest an initial trigger for future possibilities of exploration and more in-depth studies to clarify the interaction of ZnO NPs and the possible metabolic pathways triggered in these insect pests.